Caribou carving at the Northwest Territories Legislative Assembly ... - Campbell, Sandy (University of Alberta Library, 2015)
This sculpture was created by Alain Iyerak in 1970. It is made from a single vertebra of a bowhead whale. The vertebra had to dry for 100 years to be used for carving. The carving is housed on the upper level of the NWT Legislative Assembly Building. ...